Validation and reliability assessment of the Persian Adaptation of the Interprofessional Team Collaboration Scale II (P-AITCS-II) for Iranian healthcare providers - Roohangiz Norouzinia; Sara Esmaelzadeh Saeieh; Carole Orchard; Samaneh Mirzaei; Mohsen Gholinataj Jelodar (BMC Health Services Research)
Abstract The primary objective of this study was to perform a psychometric evaluation of the Persian adaptation of the Assessment of Interprofessional Team Collaboration Scale (P-AITCS-II). This methodological study aimed to assess the validity and reliability of the AITCS-II for practitioners within the Iranian healthcare context. Data were collected from a sample of 230 Iranian healthcare providers between May and June 2024. Confirmatory factor analysis demonstrated good model fit indices (χ2 = 540.20, df = 224, χ2/df = 2.41, CFI = 0.917, IFI = 0.918, TLI = 0.907, PNFI = 0.768, PCFI = 0.812, and RMSEA = 0.079 [CI90% 0.070–0.087]). These results confirm the validity of the P-AITCS-II model. Additionally, the internal consistency and composite reliability of the three factors were higher than 0.7. Convergent validity was considered acceptable for the P-AITCS-II, as the Average Variance Extracted (AVE) was greater than 0.5. The Persian adaptation of the Assessment of Interprofessional Team Collaboration Scale II (P-AITC-II), consisting of 23 items within three factors—partnership, cooperation, and coordination—demonstrated good validity and reliability. However, further research is needed to confirm its robustness and usefulness for improving interprofessional team collaboration.